The effect of taxpayer awareness, compliance, and forced letter collection on tax receiving (empirical study at Serpong primary tax service office) - Siti Nurul Akasyah; Juitania Juitania (President University, 2022)
Taxes are an important source of revenue for the state; in order to maximize tax revenues, the government expects the community to participate in fulfilling their tax obligations based on tax provisions. According to data from the Ministry of Finance, the number of taxpayers in Indonesia increased from year to year, reaching 46.38 million in 2020. This figure increased from the previous year, with 42.51 million taxpayers in 2019. In 2017, and 2018, the number of taxpayers was 36.51 million and 39.15 million. In this case, tax revenues should increase rather than decrease, because the number of taxpayers increases year after year, but tax revenue realization falls short of the predetermined target. an imbalance in the achievement of predetermined tax revenue targets with the number of registered taxpayers, which continues to grow year after year. The purpose of this study is to analyze and investigate the impact of taxpayer awareness, taxpayer compliance, and tax collection with forced letters on tax receipts at Serpong Primary Tax Service Office. This is a quantitative study that employs primary data. Individual taxpayers (WPOP) registered at Serpong Primary Tax Service Office comprise the population of this study. A total of 400 respondents were sampled using a non-probability sampling technique. Data collection methods utilizing a questionnaire This study was carried out between August and November of 2021. Multiple linear regression analysis was used in this study as the regression model. The Statistical program version 25 was used to process the data. According to the findings of this study, Taxpayer Awareness, Taxpayer Compliance, and Tax Collection with Forced Letters all have a simultaneous and partial effect on Tax Revenue.